Generation and testing of emergent traits in composite professional stereotypes - Benrós, Miguel F. (2020)
In daily interactions, we frequently meet people that belong to multiple categories, sometimes with conflicting stereotypical implications. Studies show that, when generating attributes for composite stereotypes, novel emergent attributes are created, derived from the constituent categories, but also from real world knowledge (e.g., Hastie, Schroeder, & Weber, 1990; Kunda, Miller, & Claire, 1990). In this work, in a similar vein as the work by Kunda and collaborators (1990), we test composite professional categories, and their simple constituents, in a Portuguese sample. To our knowledge, there is no evidence that, in Portuguese language, composite categories are able to generate emergent properties. We empirically explore the kind of content that is generated, and how the conflict between constituents is solved. In Experiment 1, participants described 24 pairs of composite categories and each constituent. In Experiment 2, we refined the identification of emergent attributes by asking participants to evaluate each previously generated attribute on a rating scale, for each category, constituent or composite, in a between-subject design. Results provide evidence that emergent attributes were generated and revealed a different mean rating in the composite categories that were not in their constituents. We discuss their contribution for future research delving into what kind of processes are at the basis of the creation of composite stereotypes, as well as what is the nature of its mental representation, how stable composite stereotypes are, and how consensual are they, given different possibilities in conflict resolution modes and models (e.g., Hastie et al., 1990; Kunda et al., 1990).